PHARMACOLOGICAL ACTIVITIES OF CERRADO SPECIES MAURITIA FLEXUOSA, DIPTERYX ALATA AND BYRSONIMA CRASSIFOLIA: A LITERATURE REVIEW (REMUNOM, 2025)
Brazilian Cerrado is the second largest biome in the country, and it contains many plant species of scientific interest. From this perspective, the leaves, seeds, roots, stem bark and fruits of Cerrado species are rich in bioactive substances, mainly phenolic compounds, which make them sources of functional foods and potential drugs. Among the species with significant pharmacological potential are Mauritia flexuosa (Buriti), Dipteryx alata (Baru) and Byrsonima crassifolia (Murici). The aim of this literature review was to clarify the phytochemical profile and biological properties of the species in question. Mauritia flexuosa is a fruit-bearing palm whose fruits have high levels of pro-vitamin A carotenoids, especially β-carotenes. Bark, pulp and root extracts of Mauritia flexuosa are rich in flavonoids and are characterized by their antioxidant, antimicrobial, antitumor and regenerative capacities. Dipteryx alata is a tree whose seeds are rich in phenolic compounds, lipids, insoluble dietary fiber, calcium, zinc and iron. The species has mainly been associated with antioxidant, antiproliferative, lipid-lowering, anti ophidic, antimicrobial and antileishmanial effects. Similarly, Byrsonima crassifolia, widely used in local cuisine, has antioxidant, antidepressant, hypoglycemic, antifungal and regenerative activity as its main biological properties under investigation. This species is rich in phenolic compounds, especially catechin, and has been used in traditional medicine to treat inflammatory conditions, menstrual disorders and dermatological wounds.